Examining the Role of Psychosocial Stressors in Hypertension - Komal Marwaha (Korean Society for Preventive Medicine, 2022)
Despite advances in medicine and preventive strategies, fewer than 1 in 5 people with hypertension have the problem under control. This could partly be due to gaps in fully elucidating the etiology of hypertension. Genetics and conventional lifestyle risk factors, such as the lack of exercise, unhealthy diet, excess salt intake, and alcohol consumption, do not fully explain the pathogenesis of hypertension. Thus, it is necessary to revisit other suggested risk factors that have not been paid due attention. One such factor is psychosocial stress. This paper explores the evidence for the association of psychosocial stressors with hypertension and shows that robust evidence supports the role of a chronic stressful environment at work or in marriage, low socioeconomic status, lack of social support, depression, anxiety, post-traumatic stress, childhood psychological trauma, and racial discrimination in the development or progression of hypertension. Furthermore, the potential pathophysiological mechanisms that link psychosocial stress to hypertension are explained to address the ambiguity in this area and set the stage for further research.